2007
DOI: 10.1002/ejic.200700070
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic, X‐ray Diffraction, Electrochemical, and Density Functional Theoretical Studies of (Indenyl)ruthenium Complexes Containing Dithiolate Ligands

Abstract: Halide substitution of the complexes [(Ind)Ru(L 2 )X] {Ind = η 5 -C 9 H 7 . 1: (L 2 ) = dppf [1,1Ј-bis(diphenylphosphanyl)ferrocene], X = Cl; 2: (L 2 ) = dppm [1,1Ј-bis(diphenylphosphanyl)methane], X = Cl; and 18: (L 2 ) = (CO) 2 , X = I} with the 1,1-dithiolates -S 2 CNR 2 (dialkyl dithiocarbamates for R = Me, Et, and C 5 H 10 ), -S 2 COR (alkyl xanthates for R = Et and iPr), and -S 2 PR 2 (dithiophosphinates for R = Et and Ph) showed that the lability of the indenyl ligand is influenced by the nature of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…CH 3 CN, with reversal to [2]PF 6 . Cyclic voltammetry experiments indicated that compounds 4, 5a, [5] + , [6] + , and [7] + could be oxidized in three oneelectron steps at positive potentials. The results support the hypothesis that the oxidation processes occurs at two independent (noncommunicating) sites within the molecules, most likely at the two metal ions (Ru and Fe).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…CH 3 CN, with reversal to [2]PF 6 . Cyclic voltammetry experiments indicated that compounds 4, 5a, [5] + , [6] + , and [7] + could be oxidized in three oneelectron steps at positive potentials. The results support the hypothesis that the oxidation processes occurs at two independent (noncommunicating) sites within the molecules, most likely at the two metal ions (Ru and Fe).…”
Section: Resultsmentioning
confidence: 99%
“…We had reported a precedence for similar labilizing of the Ind ligand in the reaction of 1 with dialkyl dithiocarbamates and observed that the lability of Ind depends on the incoming dithiolato ligand and the nature of the solvent medium. [7] In this context, we point out that our earlier reaction of [RuClCp(dppf)] with pyridine-2-thiol in the presence of NaBPh 4 resulted only in chlorido substitution to afford the ionic complex, [RuCp(dppf)(pySH)]BPh 4 (D) (where pySH = pyridine-2-thione), arising from thiol/thione tautomerization of pyridine-2-thiol. (Scheme 2).…”
Section: Synthesis and Reactivitymentioning
confidence: 98%
See 2 more Smart Citations